ASSESSMENT OF THE USE OF REMOTELY SENSED RAINFALL PRODUCTS FOR RUNOFF SIMULATION IN THE UPPER BLUE NILE BASIN OF ETHIOPIA - Ashenafi, Yared; Hailu, Dereje (Zede Journal of Ethiopian Engineers and Architects, 2023)
The successful application of hydrological models model verification [3], and more generally, it improves the understanding on the hydrologic cycle. Nowadays, remote sensing imagery acquired and processed in real time can provide near-realtime rainfall at relevant spatio-temporal scales (tens of kilometers and sub-daily) [2], [4], [5], [6]. Remote sensing has increasingly become a viable data source to supplement the conventional hydrological rainfall-runoff simulation, particularly for inaccessible regions or complex terrains and in areas where there are no rainfall and stream flow gauging stations [5], [6]. depends not only on the model structure and spatial and temporal scale, but also on the accuracy of the rainfall as a main input. In many developing countries like Ethiopia, the rainfall observation network is relatively sparse. In recent years, several techniques have been developed for estimating rainfall using satellite data. The Climate Prediction Center Morphing Method (CMORPH) is one of them and it uses motion vectors derived from half-hourly interval geostationary satellite infrared imagery to propagate the relatively high quality precipitation estimates derived from passive microwave data. The main objective of this research is to compare the performance of SWAT model using rainfall input data from remotely sensed and ground measured data for Gilgel abbay catchment. Based on the results obtained, it can be said that SWAT model yields good results for the satellite rainfall input data when compared to in situ rainfall input data. Thus, CMORPH rainfall products can possibly be used for the un-gauged catchment in the Upper Blue Nile Basin. It is recommended to test the CMORPH rainfall product over other catchments with relatively dense in situ data in the Upper Blue Nile Basin with the same CMORPH and finer spatial resolutions products.